IBM System Storage Tape Library guide for open systems - Coyne, Larry; Alavari, Sandor; Browne, Simon; Hoffmann, Chris; Munoz, Leticia; Schaefer, Markus (IBM Redbooks, 2013)
This IBM® Redbooks® publication presents a general introduction to Linear Tape-Open (LTO) technology and the implementation of corresponding IBM products. The IBM Enterprise 3592 Tape Drive also is described. This tenth edition includes information about the latest enhancements to the IBM Ultrium family of tape drives and tape libraries. In particular, it includes details of the latest IBM LTO Ultrium 6 tape drive technology and its implementation in IBM tape libraries. Information is included about the recently released, enhanced, higher-performance ProtecTIER servers and the features of the new version 3.2 server software. The new software also enables a new feature, the File System Interface (FSI). It also contains technical information about each IBM tape product for Open Systems. It includes generalized sections about Small Computer System Interface (SCSI) and Fibre Channel connections and multipath architecture configurations. This book also includes information about tools and techniques for library management. This edition includes details about Tape System Library Manager (TSLM). TSLM provides consolidation and simplification in large TS3500 Tape Library environments, including the IBM Shuttle Complex. This publication is intended for anyone who wants to understand more about IBM tape products and their implementation. This book is suitable for IBM clients, IBM Business Partners, IBM specialist sales representatives, and technical specialists. If you do not have a background in computer tape storage products, you might need to reference other sources of information. In the interest of being concise, topics that are generally understood are not covered in detail.